MUSLIM AND CHRISTIAN UNDERSTANDING: Theory And Aplication Of “A Common Word” - Saifurrahman Saifurrahman (Universitas Islam Negeri (UIN) Mataram, 2016)
Religious conflict reaches almost all human civilizations. There are many factors which cause it. Truth claim is one of the factors that need to be solved. Moreover, religion has become collective identity which differentiate one group from another group. Anthropology approach can assist and drive to conclusion that each religion has general pattern, in Islamic term called Kalimatun Sawa’. Kalimatun Sawa’ or a common word theoretically (love of God) or in real context (love of neighbor) could be a way out to resolve the problem of religion conflict. In the context of Indonesia, moving from debate to dialogue is a main concern of scholars. The religious leaders are expected to able to mobilize their members to corporate in many things regarding daily life. The legalized law which assures people live in peace with their neighbors is lied on government full right as the policy holders.